Financial Performance Appraisal of Adidas Group - Khatik, S. K.; Nag, Amit Kumar (Indian Journal of Research in Capital Markets, 2020)
The purpose of this study was to appraise the financial performance of Adidas during the year 2014 – 2018. Selected liquidity ratios, solvency ratios, profitability ratios, efficiency ratios, and statistical tools like t - test were used to appraise the data under consideration. The results largely suggested that overall financial performance of the company was satisfactory ; the only grey area was the liquidity ratios. The results also showed that there was significant difference in solvency position, overall efficiency, & profitability position of the company during the period under consideration. The results are based on data of last 5 years ending 2018 and only monetary information was considered. The prime objective of this investigation was to evaluate Adidas’s financial performance.